A reward-centred model of anorexia nervosa: A focussed narrative review of the neurological and psychophysiological literature - O’Hara, Caitlin B.; Campbell, Iain C.; Schmidt, Ulrike (Neuroscience and biobehavioral reviews, 2015)
This focussed narrative review examines neurobiological and psychophysiological evidence supporting a role for altered reward processes in the development and maintenance of anorexia nervosa (AN). In AN, there does not appear to be a generalised inability to experience reward. Rather, data suggest that a reluctance to gain weight leads to an aversive appraisal of food- and taste-related stimuli. As a result, cues compatible with this aberrant mode of thinking become rewarding for the individual. Evidence also suggests that attribution of motivational salience to such cues promotes anorectic behaviours. These findings are consistent with models in which interactions between cognition and reward are important in eliciting the anorectic "habit". A model is proposed which is consistent with elements of other theoretical frameworks, but differs in that its emphasis is towards neural overlaps between AN and addiction. It is consistent with AN being a reward-based learned behaviour in which aberrant cognitions related to eating and shape alter functioning of central reward systems. It proposes that the primary neural problem responsible for the development, maintenance, and treatment resistance is centred in the striatal reward system. This helps shift the emphasis of aetiological models towards reward processing, particularly in the context of illness-compatible cues. Furthermore, it suggests that continuing to explore the utility and valued nature of AN in the patient's life would be a useful inclusion in treatment and prevention models.